Mentimeter in Islamic Religious Education: A Systematic Review of Research Trends, Reported Pedagogical Impacts, and Implementation Challenges - Risdiani; Gigih Setianto; Siti Nur’aini (Al-fiqh, 2026)
This study aims to map research trends, synthesize reported pedagogical impacts, and identify implementation challenges associated with Mentimeter in Islamic Religious Education (PAI). A Systematic Literature Review (SLR) was conducted following PRISMA 2020 guidelines. Literature searches were conducted in ScienceDirect, SINTA, and Google Scholar on 15 June 2026 for publications from 2021 to 2026. Of 150 identified records, 20 studies met the inclusion criteria. The included studies covered quantitative, qualitative, and mixed-methods research, with varied sample sizes and research contexts. Data were synthesized using thematic synthesis to identify recurring patterns. Across the reviewed literature, student participation and classroom interaction were frequently reported as pedagogical outcomes associated with Mentimeter use. Several studies also reported improvements in indicators of critical and creative thinking, although the evidence varied in study design, samples, and outcome measures. Reported implementation challenges included limited technological infrastructure, lecturers’ digital competencies, and institutional readiness. Overall, the evidence suggests that Mentimeter may support participatory and interactive IRE/PAI learning environments; however, the heterogeneous evidence is insufficient to establish causal effectiveness in improving critical and creative thinking. Further multi-site, rigorous, and longitudinal studies are needed.